Thermodynamic analysis of gas turbine cycle using inlet air cooling methods - Ana Paula Pereira dos Santos (2012)
This work focuses on a comparative analysis among three compressor inlet air cooling techniques using a thermodynamic approach to simulate the gas turbine cycle. Firstly, a Base Case is tested to determine the gas turbine performance without any cooling method. The effect of site altitude on the power output gas turbine even without any cooling technique is also simulated. After, the evaporative cooling, absorption and mechanical refrigeration chillers are studied under different ambient temperature and relative humidity. Results showed that the cooling potential of the evaporative system is dependent of its effectiveness, while the absorption chiller cooling load is determined by pre-established compressor inlet air temperature. For the mechanical chiller method, however, it is necessary also to consider the power demand required by the vapour refrigerant compression. It is important to observe that although the absorption chiller has been the more suitable cooling method, it is only a realizable solution if the exhaust gases heat are available and with adequate discharge temperature. Furthermore, the gas turbine analysis is carried out at two brazilian locations: Campos/RJ and Goiania/GO. The monthly power output gain offered by the evaporative cooling method is low due to its intrinsic limitation, the ambient wet-bulb temperature. Further, the mechanical chiller system provided a considerable improvement in power output monthly results. However, the best power output increment is reached when the absorption chiller system is employed. Besides, a preliminary economic analysis showed that evaporative cooling offered the lowest unit electric energy cost, but associated with the lesser incremental power generation potential. On the other hand, the chillers systems are more expensive, while provide larger values of incremental electric energy. Results also showed that the cooling techniques allow obtaining a considerable increase in power generation with a lower cost in comparison with the gas turbine plant without any cooling method.